Two species of the genus Theristus Bastian, 1865 (Nematoda: Xyalidae) from the hypersaline water bodies of the Crimea (Azov-Black Sea basin) - Revkova, Tatiana N. (Zootaxa, 2020)
Morphological descriptions of two species of the genus Theristus Bastian, 1865 belonging to group flevensis, found in the hypersaline water bodies of the Crimean Peninsula, are presented. Theristus siwaschensis sp. n. is morphologically closest to T. flevensis Schuurmans Stekhoven, 1935, T. parambronensis Timm, 1952, T. macroflevensis Gerlach, 1954, T. metaflevensis Gerlach, 1955, but differs from them by the structure of the reproductive system in females, number of cephalic setae and size of spicules. Specimens of T. flevensis found in the Lake Chersonesskoye are similar to the re-description of a large forms of T. flevensis from Chile by Murhy (1966) and Caspian Sea by Chesunov (1981). However, it differs from the Caspian Sea species by having larger amphids, longer cephalic setae and spicules. T. pratti Murph & Canaris, 1964 and T. ambronensis Schulz, 1937 are synonymized with T. flevensis.